Clinical characteristics and risk factors for mortality in obstetric patients with severe COVID-19 in Brazil: a surveillance database analysis - Takemoto, M. L.S. [UNESP]; Menezes, M. O. [UNESP]; Andreucci, C. B.; Knobel, R.; Sousa, L.; Katz, L.; Fonseca, E. B.; Nakamura-Pereira, M.; Magalhães, C. G. [UNESP]; Diniz, C. S.G.; Melo, A. S.O.; Amorim, M. M.R. (Wiley, 2020)
Objective: To describe clinical characteristics of pregnant and postpartum women with severe COVID-19 in Brazil and to examine risk factors for mortality. Design: Cross-sectional study based on secondary surveillance database analysis. Setting: Nationwide Brazil. Population or sample: 978 Brazilian pregnant and postpartum women notified as COVID-19 Acute Respiratory Distress Syndrome (ARDS) cases with complete outcome (death or cure) up to 18 June 2020. Methods: Data was abstracted from the Brazilian ARDS Surveillance System (ARDS-SS) database. All eligible cases were included. Data on demographics, clinical characteristics, intensive care resources use and outcomes were collected. Risk factors for mortality were examined by multivariate logistic regression. Main outcome measures: Case fatality rate. Results: We identified 124 maternal deaths, corresponding to a case fatality rate among COVID-19 ARDS cases in the obstetric population of 12.7%. At least one comorbidity was present in 48.4% of fatal cases compared with 24.9% in survival cases. Among women who died, 58.9% were admitted to ICU, 53.2% had invasive ventilation and 29.0% had no respiratory support. The multivariate logistic regression showed that the main risk factors for maternal death by COVID-19 were being postpartum at onset of ARDS, obesity, diabetes and cardiovascular disease, whereas white ethnicity had a protective effect. Conclusions: Negative outcomes of COVID-19 in this population are affected by clinical characteristics but social determinants of health also seem to play a role. It is urgent to reinforce containment measures targeting the obstetric population and ensure high quality care throughout pregnancy and the postpartum period. Tweetable abstract: A total of 124 COVID-19 maternal deaths were identified in Brazil. Symptoms onset at postpartum and comorbidities are risk factors.
Keywords: COVID-19; health services accessibility; health status indicators; maternal death